Innovations in nanomaterials-based corrosion inhibitors - Kumar, Ashish; Thakur, Abhinay (IGI Global, 2024)
As industries strive for greater efficiency and longevity in their metal infrastructure, corrosion remains a persistent and costly adversary. Traditional corrosion inhibitors often fail to provide long-term protection, leading to significant economic losses and environmental harm. Innovations in Nanomaterials-Based Corrosion Inhibitors delves into a thorough exploration of the rapidly evolving field of nanomaterials and their pivotal role in corrosion inhibition. This comprehensive guide offers a transformative solution utilizing the power of nanotechnology to combat corrosion with unparalleled effectiveness.Within the pages of this book lies a wealth of knowledge meticulously curated to address the pressing need for advanced corrosion inhibition strategies. From understanding the fundamental principles of corrosion to exploring the innovative applications of nanomaterials, it equips readers with the tools to revolutionize their approach to metal protection. With a precise analysis of the synthesis, characterization, and practical implementation of diverse nanomaterials, encompassing nanoparticles, nanocomposites, and nanostructured coatings, and a primary focus on safeguarding metal surfaces against corrosion, this book creates the much-needed reference for shaping the future of corrosion inhibitors. Innovations in Nanomaterials-Based Corrosion Inhibitors offers a roadmap to overcoming corrosion challenges and heralding a new era of sustainability and cost-effectiveness. By embracing nanotechnology, industries can enhance the durability of their metal infrastructure while minimizing environmental impact and maximizing economic efficiency.